Measurement of τ polarization in W → τν decays with the ATLAS detector in pp collisions at √s = 7 TeV - Anduaga, Xabier Sebastián (2012)
In this paper, a measurement of τ polarization in W → τν decays is presented. It is measured from the energies of the decay products in hadronic τ decays with a single final state charged particle. The data, corresponding to an integrated luminosity of 24 pb−1, were collected by the ATLAS experiment at the Large Hadron Collider in 2010. The measured value of the τ polarization is Pτ = −1.06 ± 0.04 (stat) +0.05−0.07 (syst), in agreement with the Standard Model prediction, and is consistent with a physically allowed 95% CL interval [−1, −0.91]. Measurements of τ polarization have not previously been made at hadron colliders.